184k views
4 votes
Int(1 \(1 + {e}^{x} )​

User Alex Zak
by
4.8k points

1 Answer

5 votes

Answer:


\begin{aligned}\int{(1)/(1 + e^(x))\cdot dx}= x - \ln(1 + e^(x)) + C\end{aligned}.

Explanation:

The first derivative of the denominator
1 + e^(x) is
e^(x). Rewrite the fraction to obtain that expression on the numerator.


\begin{aligned}(1)/(1 + e^(x)) &= (1 + e^(x))/(1 + e^(x)) - (e^(x))/(1+e^(x))\\&=1-(e^(x))/(1+e^(x))\end{aligned}.

In other words,


\begin{aligned}\int{(1)/(1 + e^(x))\cdot dx} &= \int{dx} - \int{(e^(x))/(1+e^(x))\cdot dx}\end{aligned}.

Apply
u-substitution on the integral
\displaystyle \int{(e^(x))/(1+e^(x))\cdot dx}:

Let
u = 1 + e^(x).
u > 1.


du = e^(x)\cdot dx.


\displaystyle \int{(e^(x))/(1+e^(x))\cdot dx} = \int{(du)/(u)} = ln(|u|) = ln(u) +C = \ln{(1+e^(x))}+C.

Therefore


\begin{aligned}\int{(1)/(1 + e^(x))\cdot dx} &= \int{dx} - \int{(e^(x))/(1+e^(x))\cdot dx}\\ & = x - \ln{(1 + e^(x))}+C\end{aligned}.

User Squaregoldfish
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.